Productivity Analysis of Production Department with Objective Matrix Method - Kristine Lumban Gaol; Enny Aryanny (Journal La Multiapp, 2025)
PT XYZ is one of the international branded manufacturing companies engaged in the shoe industry and produces various brands of shoes. In 2024 the company's production on line 7 which produces Brooks brand shoes experienced a decrease in production results which caused the production target not to be achieved. From the production target of 526,624 units of Brooks brand shoes that have been targeted, line 7 production is only able to produce 473,405 units of shoes so that there is a decrease in the production of Brooks shoes by 10.10%. This research method used is Objective Matrix (OMAX). The results showed that the level of partial productivity in the production unit fluctuated with an increase and decrease in each period. Proposed improvements to increase productivity on line 7 are the establishment of a raw material inspection division with an analysis report (LA), integration of manufacturing information systems and ERP, and utilization of AI and IoT sensors for production efficiency.